The Use of Learning Models Cooperative Learning Type Student Teams Achivement Division (STAD) in Islamic Education Subjects to Increase Learning Motivation - Faqih, Muhammad Khoirul; Aziz, Ikhwan; Hayati, Rina Mida (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2025)
The aim of this research is to examine how the use of the Student Teams Achievement Division (STAD) type cooperative learning model can increase the learning motivation of class IX students in Islamic Religious Education (PAI) subjects at Tri Bhakti Assalam Integrated Islamic Middle School. The learning motivation of class IX students in Islamic Religious Education (PAI) subjects at Tri Bhakti Assalam Integrated Islamic Middle School is still low due to the lack of encouragement to study. 'This condition encourages PAI teachers to implement cooperative learning models, especially the Student Teams Achievement Division (STAD) type, in order to increase student learning motivation. Through the STAD cooperative learning model, teachers hope to change the class dynamics to be more active and collaborative, so that student learning motivation increases. This research uses a descriptive qualitative approach which focuses on analyzing the use of the Student Teams Achievement Division (STAD) type cooperative learning model in increasing students' learning motivation in holistic Islamic Religious Education (PAI) subjects. Data collection was carried out through three main techniques, namely observation, interviews and documentation. The process of testing the validity of the data carried out by the author in this research went through stages, namely: Source Triangulation and data triangulation. The research results show that the use of the STAD model significantly increases students' learning motivation in PAI subjects. The motivation that grows from relevant learning methods provides positive encouragement for students to continue to be actively involved in learning. By combining individual-based learning motivation and collective support through the STAD model, the learning process can take place more effectively, creating students who excel academically and have strong character in accordance with religious teachings.